Plan Nacional de Educación Brasileño: Mecanismo de democratización del acceso a la educación superior - Santos Alves, Higo Gabriel; de Oliveira Bernardi Noleto, Sylvana (Universidad de Costa Rica, 2022)
The purpose of this essay is to reflect on the National Education Plan (PNE) as a guiding and inducing policy of actions for the democratization of higher education in the course of the recent history of Brazilian education. Therefore, through a bibliographical and documentary research, we present some conceptual principles about plan and planning; we understand the PNE from 2001 to 2010 and the PNE from 2014 to 2024 as necessary instruments to guide Brazilian education; and we problematize their implementation processes for the democratization of access to higher education in Brazil. This essay also exposes data on the evolution of higher education enrollments in the historical series from 2002 to 2019 and relates them to access policies. As a result, we assess that, despite the structural and conjunctural limits in the field of education in Brazil, it is necessary to guarantee and validate the PNE, from the perspective of aiming for quality education, education for democracy, in order to strengthen the construction of a democratic society. Furthermore, the democratization of higher education is only effective as a public policy when there is public funding to implement the actions provided in the PNE.